A inserção do profissional da educação física nos cuidados paliativos pediátricos: uma revisão crítica da literatura - Esther Angelica Luiz Ferreira; Mateus Fabrício Pallone Manzini; Cristina Ortiz Sobrinho Valete; Cristina Helena Bruno; Claudia Aparecida Stefane (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVES: Since Pediatric Palliative Care is based on holistic and comprehensive care for pediatric patients and their families, Physical Education is an essential health area for complete interdisciplinary care. Therefore, the objective of this article is to reflect on the insertion of the Physical Education Professional in Pediatric Palliative Care. METHODS: This is a critical literature review. A theoretical and documentary research was carried out, based on the bibliographic survey in files available in the MEDLINE (via Pubmed) and SciELO databases in the last 5 years. A secondary capture was carried out from the references of the selected articles, in addition to the addition of the authors experience. RESULTS: Only 4 articles were selected in the main search, with an addition of 1 article in the secondary capture. As much as some studies suggest that increased physical activity can alleviate some symptoms, there is still a lack of robust evidence related to children. The strategies used by Physical Education Professionals must take into account the environment and the patients clinical status. The relevance of plays and games, even in the hospital setting, has been increasingly studied. CONCLUSIONS: Physical Education is an area of ??health that envisions the integrality of care, considering the inseparability of actions, both promotional and preventive, treatment and rehabilitation, which are essential aspects in Pediatric Palliative Care. Important gaps are still found, which must be addressed by education and research.